Cho đa thức `f (x) = 2x^3 – 8x^2 + 9x` Tìm nghiệm của `f (x)` 28/08/2021 Bởi Amaya Cho đa thức `f (x) = 2x^3 – 8x^2 + 9x` Tìm nghiệm của `f (x)`
`2x^3-8x^2+9x=0` `<=>x(2x^2-8x+9)=0` `TH1: x=0` `TH2:` `2x^2-8x+9=0` `<=>(2x^2-8x+8)+1=0` `<=>2(x^2-4x+4)+1=0` `<=>2(x-2)^2+1=0` Ta có: `(x-2)^2>=0` `=>2(x-2)^2=0` `=>2(x-2)^2+1>0` Vậy nghiệm của đa thức `f(x)=0` Bình luận
Ta có `:` `f(x)=0` `->` `2x^3-8x^2+9x=0` `->` Có `:` `2x^3-8x^2+9x=x(2x^2-8x+9)=0` `->` `x(2x^2-8x+9)=0` `+` Trường hợp `1` : `x=0` `+` Trường hợp `2` `:` `2x^2-8x+9=0` Vì `:` `(-8)^2-4.9.2=64-72<0` `->` PT vô nghiệm Vậy `:` Đa thức chỉ nhận nghiệm là `:` `0` `.` Bình luận
`2x^3-8x^2+9x=0`
`<=>x(2x^2-8x+9)=0`
`TH1: x=0`
`TH2:`
`2x^2-8x+9=0`
`<=>(2x^2-8x+8)+1=0`
`<=>2(x^2-4x+4)+1=0`
`<=>2(x-2)^2+1=0`
Ta có: `(x-2)^2>=0`
`=>2(x-2)^2=0`
`=>2(x-2)^2+1>0`
Vậy nghiệm của đa thức `f(x)=0`
Ta có `:` `f(x)=0`
`->` `2x^3-8x^2+9x=0`
`->` Có `:` `2x^3-8x^2+9x=x(2x^2-8x+9)=0`
`->` `x(2x^2-8x+9)=0`
`+` Trường hợp `1` : `x=0`
`+` Trường hợp `2` `:` `2x^2-8x+9=0`
Vì `:` `(-8)^2-4.9.2=64-72<0` `->` PT vô nghiệm
Vậy `:` Đa thức chỉ nhận nghiệm là `:` `0` `.`